The value of Contrast-Enhanced Ultrasound (CEUS) in the evaluation of central lung cancer with obstructive atelectasis - Zadeh, Ehsan Safai; Huber, Katharina Paulina; Görg, Christian; Prosch, Helmut; Findeisen, Hajo (Diagnostics, 2024)
Purpose: To assess the diagnostic performance of contrast-enhanced ultrasound (CEUS) alongside contrast-enhanced computed tomography (CECT) in evaluating central lung cancer (CLC). Materials and Methods: From 2006 to 2022, 54 patients with CLC and obstructive atelectasis (OAT) underwent standardized examinations using CEUS in addition to CECT. The ability to differentiate CLC from atelectatic tissue in CECT and CEUS was categorized as distinguishable or indistinguishable. In CEUS, in distinguishable cases, the order of enhancement (time to enhancement) (OE; categorized as either an early pulmonary arterial [PA] pattern or a delayed bronchial arterial [BA] pattern of enhancement), the extent of enhancement (EE; marked or reduced), the homogeneity of enhancement (HE; homogeneous or inhomogeneous), and the decrease in enhancement (DE; rapid washout [<120 s] or late washout [≥120 s]) were evaluated. Results: The additional use of CEUS improved the diagnostic capability of CECT from 75.9% to 92.6% in differentiating a CLC from atelectatic tissue. The majority of CLC cases exhibited a BA pattern of enhancement (89.6%), an isoechoic reduced enhancement (91.7%), and a homogeneous enhancement (91.7%). Rapid DE was observed in 79.2% of cases. Conclusions: In cases of suspected CLC with obstructive atelectasis, the application of CEUS can be helpful in differentiating tumor from atelectatic tissue and in evaluating CLC.
Gesehen am 10.09.2024